Laser Technology Applications in Critical Sectors: Military and Medical - Suratun Nafisah; Tukiran, Zarina; Lau Wei Sheng; Rohim, Siti Nabilah; Vincent Sia Ing Teck; Razali, Nur Liyana; Morsin, Marlia (Journal of Electronic Voltage and Application, 2021)
This study aims to observe laser technology applications in two critical sectors which are military and medical. These two crucial sectors required a technology that compatible with the nature of the field; safe, precise and fast (time –saving). A laser is defined as a device that emits a focused beam of light by stimulating the emission of electromagnetic radiation. The characteristics of lasers; coherence, directionality, monochromatic and high intensity are very suitable to be used in the critical sectors. In the military sector, the implementation of laser is commonly used in various types of weapons manufacturing. In this paper, three different military weapon systems namely weapon simulator, laser anti-missile system and navy ship laser weapon system were studied. Meanwhile, in the medical sector, the laser is widely implementing in medical equipment especially in dentistry, surgery and skin treatment. The capability of laser technology to be adapted in the critical sectors can be further investigated and enhanced for future discovery.